FOLKLORE AND SOCIAL SCIENCE LEARNING MODEL IN ELEMENTARY SCHOOL IN BALI - I Nengah Suastika; Ketut Sedana Arta; Ni Made Ary Widiastini (Universitas Gadjah Mada, 2019)
Folklore is a strategic media for the educational process, namely expository and humanistic for children. Through folklore, children have a rational, realistic perspective, values and orientation in accordance with the culture they have. However, the development of digital media with all its sophistication often removes the cultural values of children. Children lose their idol character that can be used as role models, alienated from their own cultural values and lose their identity amidst massive developments in digital information. As Bourdieu's view of habitus as a set of values, practices and inner tendencies, both structured and structured, where habitus can continue to develop (generative) and transferred from one domain to anotheR. In practice the presence of digital media turned out to have an impact on the uprooting of cultural values that should be accepted by children at an early age, because it was replaced by technological developments. Understanding this phenomenon, reinforces the ideas of Borg and Gall, in this study the development of education by utilizing folklore, not only developing an existing educational model, but also finding knowledge to solve existing problems. The learning model applied by the teacher is a learning model created by foreign experts which is often not relevant to students' cultural values. This condition is caused by the lack of local culture-based learning models, the absence of innovative efforts by teachers to develop local culture-based learning models and the lack of teachers' ability to organize and implement local culture-based learning models. By this research, Balinese folklore has a very strategic value for the development, empowerment, and preservation of Balinese customs and traditions.